Does Measurements for Internal Medical Treatments - Ali kareem Mohammed abed; Haneen Sabry Hamad Abd; Rusol Laith Hameed Abed; Aya hazem Shehab mahal; Haider Taha Khudair Hassan (Genius Journals, 2024)
Internal dosimetry is a major component of nuclear safety for the the approximately 100, 000 radiation workers at DOE radiological or nuclear facilities. Workers who handle nuclear materials or who are involved in nuclear waste management are potentially at risk of inadvertent intakes of radioactive material . DOE policy and associated radiological control programs for limiting internal effective doses are based on containment of radioactive material to ensure ( to the extent reasonably achievable) that radionuclides from work at radiological lr nuclear facilities are not taken into the body. Most significant occupations intake of radionuclides, i.e ., individuals receiving doses approaching or exceeding a limit, occur as the result of contamination incidents associated with either the inadvertent release of radioactive material in the workplace or the unplanned loss of containment .
Keywords: Internal; Medical Treatments; radioactive